2007
DOI: 10.1364/ol.32.003352
|View full text |Cite
|
Sign up to set email alerts
|

Strong UV absorption and visible luminescence in ytterbium-doped aluminosilicate glass under UV excitation

Abstract: A broad visible luminescence band and characteristic IR luminescence of Yb(3+) ions are observed under UV excitation in ytterbium-doped aluminosilicate glass. Samples made under both oxidizing and reducing conditions are analyzed. A strong charge-transfer absorption band in the UV range is observed for glass samples containing ytterbium. Additional absorption bands are observed for the sample made under reducing conditions, which are associated with f-d transitions of divalent ytterbium. The visible luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 1 publication
9
72
0
Order By: Relevance
“…At last, we showed that the thermal bleaching of PD and RD is due to hole release and recombination to Yb 2+ ions. These findings are consistent with proposals by other teams [2,[15][16][17], notably the Engholm's [15][16][17] according to which PD is due to an Yb 3+ to Yb 2+ conversion, again with hole trapping, upon absorption of a UV photon (resulting from the deexcitation of several excited Yb 3+ ions) into the charge transfer (CT) bands of Yb 3+ ions. Darkening can be bleached by photons at 3.49 eV (355 nm) [1], 2.28 eV (543 nm) [2], 1.36 eV (915 nm) [3], and 1,27 eV (980 nm, Duchez's work).…”
Section: Modelsupporting
confidence: 92%
“…At last, we showed that the thermal bleaching of PD and RD is due to hole release and recombination to Yb 2+ ions. These findings are consistent with proposals by other teams [2,[15][16][17], notably the Engholm's [15][16][17] according to which PD is due to an Yb 3+ to Yb 2+ conversion, again with hole trapping, upon absorption of a UV photon (resulting from the deexcitation of several excited Yb 3+ ions) into the charge transfer (CT) bands of Yb 3+ ions. Darkening can be bleached by photons at 3.49 eV (355 nm) [1], 2.28 eV (543 nm) [2], 1.36 eV (915 nm) [3], and 1,27 eV (980 nm, Duchez's work).…”
Section: Modelsupporting
confidence: 92%
“…The latter is though required to release a >5 eV energy and produce photo-ionization, e.g. by absorption into the charge transfer (CT) band of Yb3+ ions (yielding Yb2+ ions and trapped holes [2]). P-related centers are also formed by carrier trapping [16] and contribute to the RIA, notably in the visible and near infra-red ranges [17].…”
Section: Discussionmentioning
confidence: 99%
“…Excess optical losses are induced by external ionizing radiations (radiodarkening or RD), but also, possibly, due to the pump itself (photo-darkening, PD). PD and RD of YDF have been already well characterized [1][2][3][4][5][6][7][8][9][10][11][12], but by distinct communities. Possible interplay between PD and RD has neither been characterized nor modelled, though pumping and ionizing radiations should be at play simultaneously in some operation conditions, as in space-based applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is not unlikely that both loss mechanisms are related and that they share a common physical origin. It has been suggested that the change of valence state for the Yb-ion plays a major role for both the PD process 10 and for the nonlinear decay process. 11 The Yb-ion is known to be multivalent in many host materials, which, under intense irradiation, also could initiate charge transport resulting in color center formation and heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, it is not until quite recently that CTprocesses were observed to have a major influence on different loss processes in Yb doped high power lasers. 4,9,10 The motivation in relation to this work is to gain further understanding for different loss processes in Yb-doped laser materials in general and Yb-doped fiber lasers in particular. The choice to study CT processes in Yb:YAG single crystals is because the interpretation and analysis of CT processes and radiation induced color centers in a crystalline material is less complex when compared to that for amorphous silica glass.…”
Section: Introductionmentioning
confidence: 99%